Optical analog-signal transmission system in a dynamic and complex scattering environment using binary encoding with a modified differential method - Cao, Yonggui; Xiao, Yin; Chen, Wen (Optics express, 2023)
High-fidelity optical transmission through dynamic scattering media is challenging, since transmission errors are induced due to dynamic scattering media. In this paper, a new scheme is proposed to realize high-fidelity free-space optical analog-signal transmission in dynamic and complex scattering environments using binary encoding with a modified differential method. Each pixel of an analog signal to be transmitted is first divided into two values, and each of them is encoded into a random matrix. Then, a modified error diffusion algorithm is utilized to transform the random matrix into a 2D binary array. Each pixel of the analog signal to be transmitted is eventually encoded into only two 2D binary arrays, and transmission errors and dynamic scaling factors induced by dynamic and complex scattering media can be temporally corrected. Dynamic smoke and non-line-of-sight (NLOS) are created as a dynamic and complex scattering environment to verify the proposed method. It is experimentally demonstrated that analog signals retrieved at the receiving end are always of high fidelity using the proposed method, when average path loss ( APL ) is less than 29.0 dB. Only the half number of measurements is used compared to that in conventional methods. The proposed method could open up a novel research perspective for high-fidelity free-space optical analog-signal transmission through dynamic and complex scattering media.